Stimulasi Partisipasi Masyarakat dalam Perencanaan Pembangunan Kawasan melalui Optimalisasi Keahlian Pemetaan Menggunakan Drone - Zulkia, Dwi Rizka (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2023)
KOTAKU Bangka Regency, is a program that focuses on addressing slum areas within Bangka Regency. Improving the quality of the residential environment is a mandate from the government outlined in the 2020-2040 RPJMN (National Medium-Term Development Plan). This involves enhancing the quality of slum areas, preventing the growth of new slum settlements, and promoting sustainable living. When planning an area, spatial data is crucial to support the planning process. Currently, the available spatial data is in the form of digital maps from Google Earth, but the quality is subpar, often appearing blurry and unreadable due to cloud cover. Spatial data can be processed through aerial photos taken using drones. However, Bangka Regency's "KOTAKU" program faces several challenges, including a lack of expertise in drone-based documentation, such as capturing photos and videos, as well as mapping and processing aerial photos in Geographic Information Systems. Therefore, outreach programs on drone operation and aerial photo processing for mapping are essential to enhance the knowledge of the community, especially stakeholders involved in area planning. The method employed in this community engagement activity is POAC (Planning, Organizing, Actuating, Controlling). Evaluation, specifically in the "controlling" phase, includes providing questionnaires to assess the partners' understanding of the knowledge imparted. Based on the evaluation results, it is evident that the mapping training provided enhances the partners' knowledge and is beneficial as it addresses various issues and fulfills the partners' needs.